PEMBUATAN MAKALAH PADA MICROSOFT WORD PADA SISWAMADRASAH IBTIDAIYAH ASSADATUL 1 TANGERANG SELATAN - Aji Setya Wicaksono Aji Setya Wicaksono; Bachtiar Basuni; Elyakim Sibarani; Fadlun Kohar; Hendri Setiawan; Muhammad Iqbal Maulana; Muhammad Rizky Awaludin; Muhammad Zahir; Whempi Vazly; Rayhan Ath Thaariq; Iwan Giri Waluyo (Abdi Jurnal Publikasi, 2023)
Microsoft Word or Microsoft Office Word is Microsoft's mainstay word processing software. The current use of Microsoft Word is only part of the functions that are used, there are still many that have not been used optimally. The goal is to help elementary school students at Madrasah IbtidaiyahAssadatul 1 South Tangerang to understand Microsoft Word and functions in Microsoft Word. In this community service activitywe use the presentation method in training and production for students at Madrasah Ibtidaiyah Assadatul 1 South Tangerang as a learning medium. In this training we conducted an introduction on how to use Microsoft Word in making papers. Next, we provide material about the history of Microsoft Word so they know what changes have been made to Microsoft Word. Then we discussed the features that exist in Microsoft Word so that they can be useful for making papers. Based on the results of the Community Service that has been carried out, the results obtained are that the Students of Elementary School of Madrasah ibtidaiyah assadatul 1 South Tangerang can understand the learning provided. With students and students can make papers in Microsoft Word well.